The EU Private damages directive practical insights ; minutes of the Closed workshop 2015 - Wijckmans, Frank; Visser, Maaike; Jaques, Sarah; Nöel, Evi (Intersentia, 2016)
"These are the minutes of a Closed Workshop organized on 21 May 2015 in Brussels, Belgium and attended by a group of competition law specialists covering the majority of the EU Member States. The Closed Workshop was entirely dedicated to the EU Private Damages Directive (PDD)"...Back cover